Woolworths SA : making sustainability sustainable - Bowen, Amanda, active 2009; Luiz, John Da Silva (London : Wits Business School, 2009)
In February 2009, Justin Smith, manager of the Good business journey at Woolworths, a leading South African department store, was a worried man. Woolworths had launched its five-year sustainability strategy just under two years before. After undertaking an impact assessment, Smith was concerned that the original targets - which covered transformation, social development, the environment and climate change (see Exhibit 1) - had been set without a clear understanding of exactly what it would take to achieve them. Woolworths had recently identified 10 key risk areas that impacted on the achievement of its original goals. If the sustainability goals were not reached, Woolworths could lose credibility among its shareholders, staff and consumers. What did Woolworths need to do to ensure that it achieved its sustainability goals? And had the company been too ambitious in the targets it had set initially, he wondered?
Originally Published In Bowen, A., & Luiz, J. (2009). Woolworths SA: Making Sustainability Sustainable. WBS-2009-8. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Woolworths -- Case studies; Sustainability -- South Africa -- Case studies; Stores, Retail -- Environmental aspects -- South Africa -- Case studies; Sustainable development -- South Africa -- Case studies